Affect behind the use of anglicisms among adolescents in North Macedonia - causes and consequences - Celevska, Izabela; Naumoska Sarakinska, Biljana (The International Association for the Educational Role of Language, 2023)
As the most effective means of communication, language is open to numerous changes to adapt to its users. English both influences other languages, and is influenced by them, most often the former than the latter, especially in the area of enriching their word stock. As things change in society, and in life, the users’ needs change, too; new phenomena appear, resulting in new words entering a given language. This integration is interesting to study in more detail as it may provide an insight into the reasons and the consequences to the target language at hand. This paper looks at a small-scale study carried out among adolescents in N. Macedonia, with the aim to see how much anglicisms feature in their everyday speech, and why. Though the frequent use of anglicisms is nothing bad, awareness should be raised as it might result in the source language becoming less familiar to its native speakers, and eventually fading away.
Keywords: anglicisms, adolescents, loanwords, language planning, language use, affect